Strategies Used in the Translation into Albanian of Allusions in Walt Whitman's Poetry - Pema, Alketa (Richtmann Publishing, 2012)
A translator who examines a text with a view to translate it will have a number of concerns. Among them, allusions are likely tobecome puzzles when they cross a cultural divide. Translating allusions can be a demanding task due to the fact that theysimultaneously activate two texts and have specific meanings in the culture and language in which they arise but not necessarily inothers. However, the use of allusions by an author shows an expectation that the reader is familiar with the references made, otherwisethe effect is lost. Taking this into account, the present study focuses on personal proper noun and key phrase allusions in the poems ofthe- famous American poet Walt Whitman and their translations into Albanian. It aims to investigate how translation- strategies wouldprovide the translators, in particular the novice ones, with useful insights concerning intertextual references in general and allusions inparticular in order that the translators might find it no more challenging a task. In order to achieve the above mentioned purpose, thepersonal proper noun and key-phrase allusions in Leaves of Grass and their equivalents in the Albanian translation were first identified.Then, Leppihalme's (1997) proposed strategies for the translation of allusions were analyzed. The analysis revealed that the mostcommon strategy for the translation of personal proper nouns was that of 'retention without any guidance' and for key-phrase allusionswas that 'literal translation with minimum change'. This is indicative of the translator's wish to be as faithful as possible to the sourcetexts to demonstrate that the allusive language of the original texts and connotations conveyed by them were largely ignored by thetranslator.